Coagulation and dynamics nanoparticles in low pressure plasma jets - Kravchenko, O.Yu.; Maruschak, I.S. (Вопросы атомной науки и техники, 2019)
One of the most promising methods for creating nanostructured films is the use of plasma jets of low pressure with nanoparticles. In this case, it is important to control the size of the nanoparticles, their temperature and energy to optimize the properties of the films. In this paper, using computer simulations, a study is conducted on coagulation of nanoparticles in a plasma jet that expands into rarefied gas. In our model, we use a hydrodynamic model for describing the dynamics of a plasma with a multidisperse phase, as well as a sectional method for describing the coagulation of nanoparticles. At the entrance to the plasma torch, the plasma parameters were stationary, and the dust particles were considered the same size. Calculations were made at various concentrations of dust particles in the plasma jet. The simulation results show that nanoparticles of various sizes appear in the plasma stream as a result of coagulation. With increasing distance from the inlet, the average modulus charge and the dispersion of the charge of nanoparticles decreases due to the decrease in the temperature of the ions and, consequently, the ion current on the dust particles. Одним з найбільш перспективних методів створення наноструктурованих плівок є використання плазмових струменів низького тиску з наночастинками. При цьому для оптимізації властивостей плівок важливим є контроль за розміром наночастинок, їх температурою та енергією. У цій роботі за допомогою комп’ютерного моделювання проводиться дослідження коагуляції наночастинок у плазмовому струмені, який розширюється в розріджений газ. У нашій моделі використовуються гідродинамічна модель для описання динаміки плазми з мультидисперсною фазою, а також секційний метод для описання коагуляції наночастинок. На вхідному отворі плазмового факела параметри плазми задавалися стаціонарними, а пилові частинки вважалися одного розміру. Розрахунки проводилися при різних концентраціях пилових частинок у плазмовому струмені. Результати моделювання показують, що в потоці плазми внаслідок коагуляції з’являються наночастинки різних розмірів. Зі збільшенням відстані від вхідного отвору зменшуються середній заряд по модулю та дисперсія заряду наночастинок, що пов’язано із зменшенням температури іонів та, відповідно, іонного струму на пилову частинку. Одним из наиболее перспективных методов создания наноструктурированных пленок является использование плазменных струй низкого давления с наночастицами. При этом для оптимизации свойств пленок важным является контроль за размером наночастиц, их температурой и энергией. В работе с помощью компьютерного моделирования проводится исследование коагуляции наночастиц в плазменной струе, которая расширяется в разреженный газ. В нашей модели используются гидродинамическая модель для описания динамики плазмы с мультидисперсною фазой, а также секционный метод для описания коагуляции наночастиц. На входном отверстии плазменного факела параметры плазмы задавались стационарными, а пылевые частицы считались одного размера. Расчеты проводились при различных концентрациях пылевых частиц в плазменной струе. Результаты моделирования показывают, что в потоке плазмы вследствие коагуляции появляются наночастицы различных размеров. С увеличением расстояния от входного отверстия уменьшаются средний заряд по модулю и дисперсия заряда наночастиц, что связано с уменьшением температуры ионов и, соответственно, ионного тока на пылевую частицу.